Role of Prophylactic Transamine in Reducing Blood Loss during Elective Cesarean Delivery - Irfan, Saima; Yazdani, Tehreem; Nisar, Salma; Khawar, Maliha; Shafqat, Hira (Pakistan Armed Forces Medical Journal, 2024)
Objective: The purpose of the current research was to see how effective Tranexamic Acid is for minimizing loss of blood after elective cesarean section.Study Design: Interventional, randomized, parallel-group study.Place and Duration of Study: Department of Obstetrics and Gynecology, Pak Emirates Military Hospital, Rawalpindi Pakistan, from August 2020 to August 2021.Methodology: Computer-generated random number tables were used to assign 130 females wo were scheduled for cesareansurgery to the Study or Control groups. The research group received TXA and regular treatment, while control group received just routine care. The gravimetric technique was used to determine blood loss in both groups. The percentage difference between hemoglobin levels before and after the operation was determined, the blood loss and percentage drop in hemoglobin were the primary outcome variables. The secondary outcomes of the study include the duration of operation, adverse effects, percentage of patients who lost more than 500ml blood and require for additional uterotonics. The outcome variables were compared using the unpaired t-test and the Chi-square test.Results: Blood loss was significantly lower in the study group from placental delivery until the end of the operation. In the study group, 5(9.3%) of patients had a drop in hemoglobin of more than 10%, whereas 25(39%) of subjects had a drop of more than 10% loss of blood in the process of Lower Segment Caesarean Section.Conclusion: TXA may be administered safely and successfully in Lower Segment Caesarean Section as its use was not linked to any adverse effects.